Transcriptome analysis of tea (Camellia sinensis) leaves in response to ammonium starvation and recovery - Wang, Yu; Ouyang, Jia-Xue; Fan, Dong-Mei; Wang, Shu-Mao; Xuan, Yi-Min; Wang, Xiao-Chang; Zheng, Xin-Qiang (Frontiers in Plant Science, 2022)
The tea plant is a kind of ammonium-preferring crop, but the mechanism whereby ammonium (NH4+) regulate its growth is not well understood. The current study focused on the effects of NH4+ on tea plants. Transcriptomic analysis was performed to investigate the early- and late-stage NH4+ deprivation and resupply in tea plants shoots. Through short- and long-term NH4+ deficiency, the dynamic response to NH4+ stress was investigated. The most significant effects of NH4+ deficiency were found to be on photosynthesis and gene ontology (GO) enrichment varied with the length of NH4+ deprivation. Enriched KEGG pathways were also different when NH4+ was resupplied at different concentrations which may indicate reasons for tolerance of high NH4+ concentration. Using weighted gene co-expression network analysis (WGCNA), modules related to significant tea components, tea polyphenols and free amino acids, were identified. Hence, NH4+ could be regarded as a signaling molecule with the response of catechins shown to be higher than that of amino acids. The current work represents a comprehensive transcriptomic analysis of plant responses to NH4+ and reveals many potential genes regulated by NH4+ in tea plants. Such findings may lead to improvements in nitrogen efficiency of tea plants.